On a localization of the spectrum of a complex Volterra operator - Bekker, M. B.; Cima, J. A. (Methods of Functional Analysis and Topology, 2019)
A complex Volterra operator with the symbol g=(1+u(z)), where u is an analytic self map of the unit disk D into itself is considered. We show that the spectrum of this operator on H^p(D), 1p